2020
DOI: 10.1111/mec.15508
|View full text |Cite
|
Sign up to set email alerts
|

Genomic evidence for gene flow between monarchs with divergent migratory phenotypes and flight performance

Abstract: Monarch butterflies are known for their spectacular annual migration in eastern North America, with millions of monarchs flying up to 4,500 km to overwintering sites in central Mexico. Monarchs also live west of the Rocky Mountains, where they travel shorter distances to overwinter along the Pacific Coast. It is often assumed that eastern and western monarchs form distinct evolutionary units, but genomic studies to support this notion are lacking. We used a tethered flight mill to show that migratory eastern m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 99 publications
4
35
0
Order By: Relevance
“…Environmental contributions to migration‐associated traits may be particularly important for understanding differences observed between wild‐caught eastern and western monarchs, especially in light of studies showing that larval host plant species can influence adult monarch size (Decker, Soule, de Roode, & Hunter, 2019; Freedman, Jason, et al, 2020; Pocius et al, 2017). Environmental differences were also suggested as the reason for the significantly higher flight endurance of eastern compared to western monarchs (Talla et al, 2020).…”
Section: Ecological and Phenotypic Divergence Between Eastern And Western Monarchsmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental contributions to migration‐associated traits may be particularly important for understanding differences observed between wild‐caught eastern and western monarchs, especially in light of studies showing that larval host plant species can influence adult monarch size (Decker, Soule, de Roode, & Hunter, 2019; Freedman, Jason, et al, 2020; Pocius et al, 2017). Environmental differences were also suggested as the reason for the significantly higher flight endurance of eastern compared to western monarchs (Talla et al, 2020).…”
Section: Ecological and Phenotypic Divergence Between Eastern And Western Monarchsmentioning
confidence: 99%
“…This result is summarized in Table 1 (also reviewed in Pierce, Altizer, Chamerlain, Kronforst, & de Roode, 2015) and is robust to the kind and number of markers analyzed (i.e., microsatellites versus single nucleotide polymorphisms from whole genome sequencing) and consistent across studies. The most comprehensive study on the topic is from Talla et al (2020), who used whole genome resequencing for 14 eastern and 29 western monarchs and found no evidence for any genetic differentiation, including no fixed differences between east and west and no windows of elevated F ST in genome‐wide comparisons. While these studies are consistent with genetic panmixia between eastern and western monarchs, an alternative interpretation is recent divergence but with ongoing low levels of gene flow.…”
Section: Genetic Studies Of Differentiation Between Eastern and Western Monarchsmentioning
confidence: 99%
“…A large number (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) of individual citizen scientists in Oregon participated in this program annually, each rearing a varying number (3-600) of monarch butterflies in protected home gardens (~10% of rearers) or indoors during August-October. All captivereared monarchs were locally sourced from eggs or larvae found within Oregon, often in the back yard or property of the citizen, and were mostly reared in muslin cages on narrow-leaved milkweed (A. fascicularis Dcne.)…”
Section: Oregonmentioning
confidence: 99%
“…It is possible that western and eastern monarchs differ in their response to captive rearing. A recent study [30] showed that despite no genetic difference, eastern monarchs are capable of superior flight performance in the laboratory compared to western monarchs. It is also possible that the more modest migration of western compared to eastern monarchs may serve to mask any negative influences of captiverearing if they exist.…”
Section: Length Of Life Of Tagged Monarchsmentioning
confidence: 99%
See 1 more Smart Citation